Reflections on the interpretation and application of the due diligence obligation in international climate litigation: a comparative study of Daniel Billy et al. v. Australia and the COSIS advisory opinion - Liang, Shiqi (Frontiers in Marine Science, 2024)
This article examines the interpretation and implementation of due diligence obligation in international climate litigation and advisory opinions, specifically by comparing Daniel Billy et al. v. Australia and the COSIS Advisory Opinion. It offers insights into the definition of due diligence obligation, the criteria for breach, and the remedies available under various legal frameworks. The due diligence obligation is not solely a direct duty under a specific treaty; it also imposes a positive obligation of conduct that must be evaluated within a broader legal framework. This method facilitates systemic integration. It facilitates the citation of pertinent regulations and precedents from different domains of international law during treaty interpretation. This approach promotes the harmonization and integration of various legal systems. The essay performs a comparative analysis of two cases. It analyses the implementation of the due diligence obligation in the realms of environmental and human rights protection. The emphasis is on the legal responsibility of States about climate change. The paper ultimately outlines the significance of the two instances for the future of international environmental law and the protection of human rights, highlighting the crucial role of due diligence responsibilities in combating climate change.